The effect of special mental exercises to develop the accuracy of the performance of some basic skills for youth futsal players - Hammad, Salah Hadi; Abdulrahman, Mohammed Abdulqader; Najim, Layth Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to add mental exercises in the training curriculum and to identify their impact on the variables of the research under study. The experimental design on a sample of (18) players were distributed to two experimental and control groups equally. The development of the skills under study, and the recommendations of the adoption of mental exercises in the stage of special preparation in the training curricula for young people by trainers.